The Effect of Student Participation in Student Organizations on Soft Skills Development: A Case Study at UINSU - Rahma Wati, Desi Indriani (AMK : Abdi Masyarakat UIKA, 2023)
Higher education plays a central role in preparing students to face increasingly complex work environments. The focus on soft skills has grown, with communication, leadership, interpersonal skills and adaptability being key in increasing students' competitiveness in the world of work. In a university environment, student organizations are a potential forum for developing soft skills. However, the question arises to what extent participation in student organizations contributes to the development of these skills. This research explores the influence of student participation in student organizations on the development of soft skills at UIN North Sumatra (UINSU) through case studies. It is hoped that the results of this research will provide important insights into the role of student organizations in preparing students with relevant skills to face career challenges. This study involved around 30 students active in student organizations at UINSU using the interview method and maintaining research ethics and privacy of respondent data. It is hoped that this research will provide useful insights regarding the development of student soft skills in higher education.